(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Concrete, which makes up most of cement, emanates a lot of carbon dioxide, concrete has a wonderful ecological effect. Assuming that how much concrete utilized in assembling of cement is limited by the utilization of mineral admixtures without compromising solidness standards, decreasing the natural effect of concrete is conceivable.